ANALISIS FAKTOR-FAKTOR PENENTU HARGA JUAL IKAN DAN IMPLIKASINYA TERHADAP KESEJAHTERAAN NELAYAN DI DAERAH PESISIR SELATAN YOGYAKARTA - Nisaul Maghfiroh (Journal of Economic and Business Analysis, 2024)
Abstract: This study aims to analyze the factors influencing fish selling prices and their impact on the welfare of fishermen in the southern coastal areas. The research method used is to examine theories conceptually to identify factors influencing fish selling prices, such as fish size, season, market access, and others. The data used are sourced from previous studies and then linked to market uncertainty theory as an analysis of market dynamics. The results of the analysis based on theory show that demand and supply, production costs, and consumption trends have a significant influence on fish selling prices and consequently affect the welfare of fishermen. However, this study also identifies some limitations, including reliance on secondary data and limitations of the analytical model used. Discussion of the research limitations provides guidance for further research that is more comprehensive and holistic in understanding the dynamics of the local fish market.